ChemInform Abstract: "The Green Side of the Moon: Ecofriendly Aspects of Organoselenium Chemistry". Issue 47 (6th November 2014) - Santoro, Stefano; Azeredo, Juliano B.; Nascimento, Vanessa; Sancineto, Luca; Braga, Antonio L.; Santi, Claudio
Abstract Review: [key aspects for the development of a greener synthesis and the use of organoselenium compounds; 98 refs.